The Effect of PjBL Model Assisted by Revit Application on Students' Building Drawing Learning Outcomes in the DPIB Department at SMK Negeri 4 Palembang - Sahera Silvia Vaesar; Muhammad Giatman; Fahmi Rizal; Elfizon; Abdul Habib Arrasyidi Desky (Postgraduate, University of Mataram, 2026)
Building drawing instruction in vocational secondary schools (SMK) continues to face significant challenges, particularly low student learning outcomes attributed to teacher-centered approaches and suboptimal integration of industry-relevant technology. This study aims to analyze the differences in building drawing learning outcomes across cognitive, psychomotor, and affective domains between students taught using the Project Based Learning (PjBL) model assisted by Revit and those receiving conventional instruction in the DPIB department at SMK Negeri 4 Palembang. A quantitative quasi-experimental design with Non-Equivalent Control Group and pretest–posttest procedure was employed. Subjects were Grade XII DPIB students in the 2024/2025 academic year: experimental group (n = 32) and control group (n = 30). Data were collected through cognitive tests, project assessment rubrics, and attitude questionnaires, then analyzed using independent and paired sample t-tests after fulfilling normality and homogeneity requirements, with effect size measured by Cohen's d. The PjBL-Revit model was implemented at a very good level (88.89%). Cognitive outcomes differed significantly between experimental (M = 89.91) and control groups (M = 67.27), with p < 0.05 and a very large effect size (Cohen's d = 4.74). Psychomotor outcomes also differed significantly (experimental: M = 77.95 vs. control: M = 65.40), as did affective outcomes (experimental: M = 3.14/4.00 vs. control: M = 2.71/4.00). These findings confirm that PjBL assisted by Revit not only enhances technical drawing competencies but also aligns vocational training with digital construction industry standards.